Theoretical Study on Methylated Resveratrol Analogues towards the Antioxidant Activity and Mechanisms: Understanding the Structure–Activity Relationship - Pei, Ling (Russian Journal of Physical Chemistry A, 2023)
Theoretically, the antioxidant properties of substances are usually evaluated by three working mechanisms, including H-atom transfer (HAT), single-electron transfer-proton transfer (SET-PT), and sequential proton loss electron transfer (SPLET). In this paper, the antioxidant activity of resveratrol and methyl derivatives (1-4,4-methylresveratrol) in the gas phase and solvents were investigated by using density functional theory (DFT). Results show that 4'-OH is still the most crutical active site of resveratrol and its derivatives. The increased number of methyl groups can enhance the antioxidant activity of resveratrol. It was also found that in the gas phase and non-polar solvents, HAT was the dominant reaction mechanism. In polar solvents, SPLET is the dominant reaction mechanism.